IMPLEMENTASI METODE SIMPLE ADDITIVE WEIGHTING UNTUK PENGUKURAN KINERJA KARYAWAN - Hery Mustofa Mustofa; Syaiful Bakhri (Jurnal Informatika dan Rekayasa Elektronik, 2022)
Employee performance appraisal system is used to assess employees who have good performance. The agency or company conducts performance appraisals on employees to evaluate, motivate, verify and improve employee performance. The decision support system will assist the company in the process of evaluating employees quickly and objectively. The simple additive weighting (SAW) method is one of the good methods and can be applied in the decision-making system. From the research results, it is known that the simple additive wighting (SAW) method can determine employee performance appraisals using four criteria, namely attendance, behavior, workload, and work realization. The highest ranking value is obtained with a value of 86.25, while the lowest value is obtained with a value of 66.6.